A Study on Engagement of Students Enrolled through Lateral Entry under the Provisions of RTE Act, 2009 - Chakraborty, Sushmita; Deepmala, (INDIAN EDUCATIONAL REVIEW, 2015)
The paradigm shift in school education as emphasised in the National Curriculum Framework (NCF), 2005 has reinforced that the students in the school need to be perceived as a dynamic participant in the construction of her/his knowledge. With the emphasis on ‘Education for All’ and after the implementation of the Right of Children to Free and Compulsory Education Act (RTE), 2009, ‘all’ children are entitled to have access to and opportunity for completion of elementary education. To achieve these goals, the importance of making learning environment adequately engaging has gained importance. The RTE mandates to ensure that not only every child has access to school, but also completes elementary education. It also expects the school to become ‘the enabling and conducive environment’ which facilitates and motivates a child to complete his/her education. Besides the extrinsic support through special training provision, it is necessary to ensure that students become intrinsically motivated and feel engaged with their school and with learning. This research attempted to identify factors influencing engagement of students who have been admitted to grades appropriate to their age in the schools in the light of RTE Act 2009.